2020
DOI: 10.1109/jstars.2020.3033591
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SMAP Core Validation Site Representativeness Errors Using Dense Networks of In Situ Sensors and Random Forests

Abstract: In order to validate its soil moisture products, the NASA Soil Moisture Active Passive (SMAP) mission utilizes sites with permanent networks of in situ soil moisture sensors maintained by independent calibration and validation partners in a variety of ecosystems around the world. Measurements from each core validation site (CVS) are combined in a weighted average to produce an estimate of soil moisture at a 33-km scale that represents the SMAP's radiometer-based retrievals. Since upscaled estimates produced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…These temporary measurements are useful as a reference for the permanent network measurements. As expected, SM measurements from the permanent and temporary networks were very well correlated overall, but the absolute SM difference ranged from 0.009 m 3 /m 3 to 0.034 m 3 /m 3 [93], which supports the finding by [77] that significant uncertainties in absolute SM remain even with relatively dense spatial sampling.…”
Section: Calibrationsupporting
confidence: 84%
“…These temporary measurements are useful as a reference for the permanent network measurements. As expected, SM measurements from the permanent and temporary networks were very well correlated overall, but the absolute SM difference ranged from 0.009 m 3 /m 3 to 0.034 m 3 /m 3 [93], which supports the finding by [77] that significant uncertainties in absolute SM remain even with relatively dense spatial sampling.…”
Section: Calibrationsupporting
confidence: 84%
“…These temporary measurements are useful as a reference for the permanent network measurements. As expected, SM measurements from the permanent and temporary networks were very well correlated overall, but the absolute SM difference ranged from 0.009 to 0.034 m 3 /m 3 [98], which supports the finding by Chen et al [82] that significant uncertainties in absolute SM remain even with relatively dense spatial sampling.…”
Section: B Core Validation Sitessupporting
confidence: 87%
“…Based on this estimation, statistical evaluation of these models is tabulated in Based on this comparison, it can be observed that different models are useful for different application requirements. For instance, in terms of accuracy as observed from figure 5, DBN RBM [2], CRNS [3], SMAP RF DN [19], GOFCHS [27], TDR [28], and P Band & L Band [34] models outperform other models, thus, they can be used for highly accurate moisture detection applications. Similarly, cost of deployment & computational complexity is visualized from figure 6, wherein it is observed that HPCM [6], HF RFID TFS [9], PWM [10], PMMA [15], FFCSM [16], MHPS [21], ECT [24], PQCWC [25], and HSAAA [32] require lowest deployment cost, while HPCM [6], PHS [17], ECT [24], and PQCWC [25] have lower computational complexity when compared with other models.…”
Section: Discussionmentioning
confidence: 92%
“…These models utilize high-speed sensors, which might be costly, but provide quicker results when compared with other sensing models. Similarly, scalability of these models is also evaluated, which indicates that CM [11] has the highest scalability, which is followed by DBN RBM [2], SMAP [18], SMAP RF DN [19], GOFCHS [27], SAR [29], SMI MODIS [30], SSMDI [33], P Band & L Band [34], and MSNs [39] models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation